Customary Mediation Practices: Practical Experiences from Indonesia - Gayo, Sabela (International Asia Of Law and Money Laundering (IAML), 2024)
The current view of society no longer sees that the court is the only dispute resolution institution. The existence of court institutions has been indicated by various cases of corruption, collusion, and nepotism, better known as KKN. This is given that many products of court decisions deviate from the principles of justice, are quick and inexpensive. In this context, an alternative dispute resolution model is needed in the customary law community that is more efficient, fair and accommodating in order to maintain the continuity and sustainability of the life of the customary law community, which is more humane and equitable. The tradition of dispute resolution in customary law communities is based on the value of the philosophy of togetherness (communal), sacrifice, supernatural values, and Justice. In customary law Community, common interest is a philosophy of life that permeates every member of the indigenous community. The practice of customary mediation in this paper in practice, the karo people of North Sumatra and papu is a form of local wisdom in resolving disputes or conflicts in Customary Law communities with a community mediation approach where in Community Mediation, leaders (customary leaders) have an important role and must have skills in resolving disputes using customary rules contained in Indigenous communities. The purpose of adat mediation practices in Indonesia is the existence of community adat mediation to maintain the balance and harmony of Indigenous Peoples by prioritizing deliberation rather than dispute resolution through legal channels.